Polygalasaponin F ameliorates middle cerebral artery occlusion-induced focal ischemia / reperfusion injury in rats through inhibiting TXNIP/NLRP3 signaling pathway - Chen, Yao; Li, Hanzhou; Yang, Yan; Feng, Lei; Yang, Ling; Zhao, Jie; Xin, Xiaochi; Lv, Shuquan; Fang, Xixing; Wen, Weibo; Cui, Youxiang; Cui, Huantian (Journal of neuroimmunology, 2024)
Polygalasaponin F (PGSF), an oleanane triterpenoid saponin extracted from Polygala japonica, has been demonstrated with neuroprotective effect. However, the therapeutic effects and mechanisms of PGSF on focal ischemia remain unknown; In this study, male Sprague Dawley (SD) rats aged 6–8 weeks were initially selected to establish a rat model of middle cerebral artery occlusion (MCAO) to evaluate the therapeutic effect of PGSF intervention and to investigate the impact of PGSF on the thioredoxin-interacting protein/NOD-, LRR-, and pyrin domain-containing protein 3 (TXNIP/NLRP3) inflammatory pathway. Secondly, brain neuron cells were isolated, and the cells received oxygen-glucose deprivation/reoxygenation (OGD/R) culture to establish the cell injury model in vitro. The mechanism of PGSF on the TXNIP/NLRP3 pathway was further validated; Our results showed that PGSF treatment reduced neurological scores, brain tissue water content and infarct volume and ameliorated the pathological changes in cerebral cortex in MCAO-induced focal ischemia rats. The TNF-α, IL-1β and IL-6 levels decreased in MCAO-induced focal ischemia rats after PGSF treatment. Moreover, PGSF down-regulated the protein expressions of TXNIP, NLRP3, ASC, cleaved caspase-1, IL-1β, and IL-18 in MCAO-induced focal ischemia rats. Meanwhile, PGSF treatment inhibited apoptosis, and reduced the levels of ROS, inflammatory cytokine and TXNIP/NLRP3 pathway-related proteins (TXNIP, NLRP3, ASC, cleaved caspase-1, IL-1β, and IL-18) in OGD/R-induced neuronal injury cells. Finally, PGSF treatment also disrupted the interaction between NLRP3 and TXNIP in vitro; Our study demonstrated the therapeutic effects of PGSF on MCAO-induced focal ischemia rats. Moreover, the neuroprotective mechanism of PGSF on focal ischemia was associated with the inhibition of TXNIP/NLRP3 signaling pathway. [Display omitted] •This study demonstrates, for the first time, the therapeutic effect of PGSF on ischemic stroke.•The investigation explores the impact of PGSF on the TXNIP/NLRP3 inflammatory pathway in rats with MCAO-induced focal ischemia.•The study further validates the mechanism of PGSF on the TXNIP/NLRP3 pathway in vitro using an oxygen-glucose deprivation/reoxygenation (OGD/R)-induced neuronal injury model.•PGSF has neuroprotective effects on rats with MCAO-induced focal ischemia, and its mechanism is associated with the inhibition of the TXNIP/NLRP3 signaling pathway.